1995
DOI: 10.1177/095646249500600409
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Candidate Virucidal Agents, Low pH and Genital Secretions against HIV-1 In Vitro

Abstract: The effect of low pH, normally present in the female genital tract, on HIV viability was examined. HIV is more acid stable than previously reported with no substantial reduction in infectivity occurring until pH levels are reduced below 4.5. The virucidal activity of 3 topical spermicides and chlorhexidine was assessed in vitro using previously established and newly modified assay systems. None of the agents tested had a selectivity index (SI) greater than 5.2. Semen and cervical secretions were assessed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 24 publications
3
47
0
3
Order By: Relevance
“…The intersubject variation in anti-HIV-1 activity shown with all mucosal fluid types in this study is consistent with intersubject variation observed in previous studies with saliva (6,10,24,54) and seminal fluid (32). However, the finding that intersubject variation also occurs in fluids other than saliva and seminal fluid has not previously been demonstrated.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The intersubject variation in anti-HIV-1 activity shown with all mucosal fluid types in this study is consistent with intersubject variation observed in previous studies with saliva (6,10,24,54) and seminal fluid (32). However, the finding that intersubject variation also occurs in fluids other than saliva and seminal fluid has not previously been demonstrated.…”
Section: Discussionsupporting
confidence: 79%
“…Poly-L-lysine hydrobromide (50 l of 50 g/ml; Sigma) was used to coat 96-well microtiter plates at room temperature for 1 h. HIV-1 RF (50 TCID 50 s in 25 l of growth medium) was added to each well and incubated for 1 h at room temperature to allow HIV-1 binding. Each mucosal fluid sample (50 l) was added in duplicate and incubated at 37°C in 5% CO 2 for 1 h. All seminal fluid samples were assessed for anti-HIV-1 activity at a dilution of 1:50 with growth medium to avoid cytotoxicity (32). C8166 cells were then added at a concentration of 4 ϫ 10 4 cells in 300 l growth medium and incubated at 37°C in 5% CO 2 for 72 h. Plates were washed three times with PBS between all stages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seminal fluid and whole semen have demonstrated anti-HIV activity in vitro in T-lymphocyte cell lines. 54 Cationic polypeptides contained in seminal plasma 55 and reactive oxygen species produced by seminal leukocytes and spermatozoa 56 provide intrinsic antiviral activity against HIV-1. Seminal plasma also blocks the attachment of HIV-1 to DC-SIGN, thus preventing viral transfer to CD4 + target cells in vitro.…”
Section: Semen-associated Factors Modulating Hiv Transmissionmentioning
confidence: 99%